CANDIED WATERMELON. INDUSTRIAL RAW MATERIALS (SPECIFICATIONS) - L. V. Pavlov; I. Yu. Kondratyeva; T. A. Sannikova; V. A. Machulkina (Овощи России)
The purpose of the standard is the valuation of the indicators of quality of candied fruit watermelon, cooked in sugar syrup, dried and coated in granulated sugar intended for industrial processing and nutrition. This standard is developed for the first time in the Russian Federation.